The Impact and Trust of The Sumbersuko Community on The Three Sources - Meyvani Chintyandini; Eggy Fajar Andalas (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Trust is a culture born and attached to the community that owns it. One of the beliefs that live in the community is the belief about Sumber Dawet, Sumber Kambang and Sumber Towo in Sumbersuko village, Purwosari sub-district. This study aims to 1) find out the stories that developed in the community regarding the origins of the three sources; 2) Community trust in the three sources in Sumbersuko village; 3) The impact caused by the existence of trust in three sources in Sumbersuko village. This research is descriptive research with a qualitative approach. The data source for this research is the people in Sumbersuko village, Purwosari sub-district, used as informants. The data of this research are in the form of observations: a) research location, b) resource persons (caretaker and the surrounding community), c) caretaker writing, d) condition of the three sources (Sumber Dawet, Sumber Kambang and Sumber Towo). Data collection procedures were carried out in various ways, namely a) Observation, b) Interview, c) Documentation, d) Recording, and e) Notes. The study results indicate various beliefs that live in the Sumbersuko village community towards these three sources, which will later affect how people think, act, and behave. The existence of a belief will give birth to an impact on people's lives. So it can be concluded that the people of Sumbersuko village still believe in the existence of ancestors and other supernatural things that still inhabit the three sources. This is still evident in their view of the sacred places in the form of these three sources.